Intergenerational discounting: A new approach - Stefan Bayer (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1998)
In this paper, we analyze how to utilize discount rates in intergenerational projects. Firstly, neoclassical decision-making is depicted in Ramsey and overlapping-generations models (OLG-models). Afterwards we investigate the utilization of time preference rates and opportunity cost rates in an intergenerational framework. The results lead us to the formulation of an adjusted OLG-discounting method of consumption units, taking into consideration intra- and intergenerational aspects. At the end of our paper, we draw some conclusions concerning environmental and resources policy, and sustainability.
urn:nbn:de:bsz:21-opus-21511
Keywords: D5; D6; D9; H4; O1; Q2; Q3; 330; Discounting; Time Preference Rate; Opportunity Cost Rate; Overlapping Generations; Zeitpräferenz; Overlapping Generations; Opportunitätskosten; Abzinsung; Umweltökonomik; Theorie